A opinião do auditor na questão da continuidade - Cunha, Cátia Cristina de Jesus Moreira (2022)
The going concern assumption is a fundamental principle in the preparation of financial statements, which indicate that an entity is generally considered from a going concern perspective, in its foreseeable future, with no intention of liquidation. The auditor's assessment of the going concern assumption has been increasingly demanding. On the one hand, as a result of the worldwide financial scandals in recent years, the auditor has been the target of criticism and questioning about his ability to identify situations of alert relating to continuity. On the other hand, this is one of the most difficult and subjective assessments for an auditor, due to its impact, assessing whether or not a company has the capacity to continue its activity can place the company in an even more delicate situation than it is already in. In this context, this work aims to understand how auditors, in the course of their work, assess the continuity of the company, and which indicators - whether economic or non- economic - lead them to consider that the assumption of continuity is found. in cause. The empirical study was developed through a qualitative work, using the content analysis of interviews carried out with several Statutory Auditors, in order to obtain their opinion regarding the way they analyze the continuity assumption and the importance attributed theme in the course of their work.